2005
DOI: 10.2473/shigentosozai.121.597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jarosite on the Removal of Arsenic ions in Sulfuric Acid Solution

Abstract: by Yuichi TOMIOKA This study investigated the role of jarosite in arsenic removal using flask shaking experiments in diluted sulfuric acid solutions (pH1-3). Jarosite was synthesized and the chemical composition of the jarosite was K 0.54 (H 3 O) 0.46 Fe 2.38 (SO 4 ) 2 (OH) 6 . The shaking experiments found that As(V) was removed by the jarosite but As(III) was not removed. The mechanisms of As(V) removal were adsorption on the jarosite and co-precipitation with Fe(III) extracted from jarosite. The removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In the case of goethite, the effects of pH, initial arsenic concentration or the presence of other elements (silicic acid, dissolved organic carbon (DOC) or sulphate) on its arsenic sorption capacity have been reported in the literature. As regards jarosite, there have been few studies on its sorption capacity [20,21]. Likewise, there is little bibliography on arsenic sorption in highly acidic conditions with the result that the relative ability of jarosite and goethite to retain arsenic remains unclear [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of goethite, the effects of pH, initial arsenic concentration or the presence of other elements (silicic acid, dissolved organic carbon (DOC) or sulphate) on its arsenic sorption capacity have been reported in the literature. As regards jarosite, there have been few studies on its sorption capacity [20,21]. Likewise, there is little bibliography on arsenic sorption in highly acidic conditions with the result that the relative ability of jarosite and goethite to retain arsenic remains unclear [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given that inorganic aqueous arsenic is an environmental and human health concern world-wide, a number of studies have addressed the use of different adsorbents [10] including schwertmannite [11,12], goethite [13][14][15][16][17][18][19], and jarosite [20,21] in an attempt to reduce its aqueous concentration. In the case of goethite, the effects of pH, initial arsenic concentration or the presence of other elements (silicic acid, dissolved organic carbon (DOC) or sulphate) on its arsenic sorption capacity have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, focused on jarosite [KFe 3 (SO 4 ) 2 -(OH) 6 ], which forms under acidic conditions and adsorbs As. [4][5][6] It has been reported that the addition of jarosite into As-containing solutions enables the removal of pentavalent arsenic [As(V)]; but trivalent arsenic [As(III)] is difficult to remove. 5) The removal of As(III) requires the oxidation of As(III) to As(V) using oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the co-occurrence of iron and arsenic can lead to the formation of hydrous iron oxides containing significant amounts of arsenic . Dissolved arsenic is often adsorbed by iron hydrosulfate, oxyhydroxides, and hydroxides such as jarosite [KFe 3 (SO 4 ) 2 (OH) 6 ] , , schwertmannite [Fe 8 O 8 (OH) 6 SO 4 ] , hematite (α-Fe 2 O 3 ) , goethite (α-FeOOH), and lepidocrocite (γ-FeOOH) . In addition, Vëronique et al found that synthesized Fe(III) phosphate, either amorphous or crystalline, can remove arsenic from waters.…”
Section: Introductionmentioning
confidence: 99%